ClCRY2 facilitates floral transition in Chrysanthemum lavandulifolium by affecting the transcription of circadian clock-related genes under short-day photoperiods. Issue 1 (December 2018) - Yang, Li-wen; Wen, Xiao-hui; Fu, Jian-xin; Dai, Si-lan
Abstract Plants sense photoperiod signals to confirm the optimal flowering time. Previous studies have shown thatCryptochrome2 (CRY2 ) functions to promote floral transition in the long-day plant (LDP)Arabidopsis ; however, the function and molecular mechanism by whichCRY2 regulates floral transition in short-day plants (SDPs) is still unclear. In this study, we identified aCRY2 homologous gene, ClCRY2, fromChrysanthemum lavandulifolium, a typical SDP. The morphological changes in theC. lavandulifolium shoot apex andClFTs expression analysis under SD conditions showed that adultC. lavandulifolium completed the developmental transition from vegetative growth to reproductive growth after eight SDs. Meanwhile, ClCRY2 mRNA exhibited an increasing trend from 0 to 8 d of SD treatment.ClCRY2 overexpression in wild-type (WT)Arabidopsis andC. lavandulifolium resulted in early flowering. The transcript levels of theCONSTANS-like (COL ) genesClCOL1, ClCOL4, andClCOL5, andFLOWERING LOCUS T (FT ) homologous geneClFT1 were upregulated inClCRY2 overexpression (ClCRY2- OE)C. lavandulifolium under SD conditions. The transcript levels of some circadian clock-related genes, includingPSEUDO-REPONSE REGULATOR 5 (PRR5 ), ZEITLUPE (ZTL ), FLAVIN-BINDING KELCH REPEAT F-BOX 1 (FKF1 ), andGIGANTEA (GI-1 andGI-2 ), were upregulated inClCRY2- OEC. lavandulifolium, while the expression levels of other circadian clock-related genes, such asEARLY FLOWERING 3 (ELF3 ), ELF4, LATE ELONGATED HYPOCOTYL (LHY ), PRR73, andREVEILLE8 (RVE8 ), were downregulated inClCRY2- OEC. lavandulifolium under SD conditions. Taken together, the results suggest thatClCRY2 promotes floral transition by fine-tuning the expression of circadian clock-related gene, ClCOL s andClFT1 inC. lavandulifolium under SD conditions. Genetics: Harnessing flower power in chrysanthemums Researchers have identified the genes that control the timing of flowering in chrysanthemums. For most plants, day-length indicates that it is time to flower. Greenhouse growers can produce out-of-season flowers by manipulating day length, but the process is expensive. Breeding varieties that respond more quickly could reduce costs, but requires a better understanding of the underlying genetics, especially in the subset of plants triggered by short days. Si-lan Dai and co-workers at Beijing Forestry University in China investigated which genes trigger flowering inChrysanthemum lavandulifolium, a typical short-day plant. They found that flowering of chrysanthemum is controlled by a gene previously identified in long-day plants, and that amplifying the gene produced plants that flowered much sooner than ordinary plants. These findings may help in breeding varieties that are easily induced to bloom.